2017
DOI: 10.1074/jbc.m116.757666
|View full text |Cite
|
Sign up to set email alerts
|

Central Regulatory Role for SIN1 in Interferon γ (IFNγ) Signaling and Generation of Biological Responses

Abstract: Edited by Charles E. SamuelThe precise signaling mechanisms by which type II IFN receptors control expression of unique genes to induce biological responses remain to be established. We provide evidence that Sin1, a known element of the mammalian target of rapamycin complex 2 (mTORC2), is required for IFN␥-induced phosphorylation and activation of AKT and that such activation mediates downstream regulation of mTORC1 and its effectors. These events play important roles in the assembly of the eukaryotic translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…IFNγ initiates its biological activities by binding to its cognate heterodimeric cell surface receptor, composed of two ligand binding IFN-gamma receptor 1 (IFNGR1) subunit chains and two signal-transducing IFNGR2 chains (4). This interaction triggers activation of several downstream signaling events, including the canonical Janus kinase (JAK)-STAT1 pathway, and non-STAT pathways, such as mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K), mechanistic target of rapamycin complex 2 (mTORC2), calcium/calmodulin-dependent protein kinase II (CaMKII), and nuclear factor kappa-B (NF-kB) cellular pathways (3,5,6,7,8). Although IFNγ-mediated activation of STAT1 is required for several IFNγ-dependent antiviral responses, some of these activities are STAT1-independent, which implies that there may be activation of alternate and complementary pathways by IFNγ stimulation during a viral infection (3).…”
Section: Introductionmentioning
confidence: 99%
“…IFNγ initiates its biological activities by binding to its cognate heterodimeric cell surface receptor, composed of two ligand binding IFN-gamma receptor 1 (IFNGR1) subunit chains and two signal-transducing IFNGR2 chains (4). This interaction triggers activation of several downstream signaling events, including the canonical Janus kinase (JAK)-STAT1 pathway, and non-STAT pathways, such as mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K), mechanistic target of rapamycin complex 2 (mTORC2), calcium/calmodulin-dependent protein kinase II (CaMKII), and nuclear factor kappa-B (NF-kB) cellular pathways (3,5,6,7,8). Although IFNγ-mediated activation of STAT1 is required for several IFNγ-dependent antiviral responses, some of these activities are STAT1-independent, which implies that there may be activation of alternate and complementary pathways by IFNγ stimulation during a viral infection (3).…”
Section: Introductionmentioning
confidence: 99%
“…5f). mTORC2-independent roles of SIN1 have been described 43,44 . We therefore generated KD of another member of mTORC2, RICTOR in hESC and found that a decrease of RICTOR expression also downregulated P-AKT(S473) and P-S6 during primed transition, mimicking SIN1 mutant phenotype in cells exiting the naïve state (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, we cannot rule out that the binding of FLCN to SIN1 in naïve hESC could also regulate mTORC2-independent functions of SIN1 (refs. 43,44 ). It is possible that FLCN may not directly interact with mTORC2 but rather may sequester SIN1 from this complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, targeted disruption of Sin1 led to decreased activation of the STAT1 signaling pathway and type I IFN-induced gene transcription in antiproliferative responses [ 90 ]. More recently, it was found that Sin1 could regulate IFNγ-induced genes and type II IFN-mediated biological responses via both Akt/mTORC1 activation and tyrosine phosphorylation of STAT1 [ 91 ].…”
Section: Sin1 Is a Conserved Adaptor Molecule Essential For Mtorc2 Functionmentioning
confidence: 99%
“…Apart from mediating the development of immune cells, Sin1 also contributes to the formation of a specific microenvironment in bone marrow as knockdown of Sin1 at mRNA level reduces low-dose irradiation-induced Akt Ser473 phosphorylation and subsequent responses in mouse osteoblasts, which inhibit osteoblast differentiation [ 107 ]. Sin1 may also regulate multiple cytokine-induced pathways since dysregulation of Sin1 led to decreased STAT1 and suppressed the transcription of several IFN-γ-induced genes [ 91 ]. As discussed above, Sin1 could also regulate type I IFN production and its antitumor responses [ 89 ].…”
Section: Physiological Function Of Sin1mentioning
confidence: 99%